Paratyphoid Fever A: Infection and Prevention - Xie, Lei; Ming, Lan; Ding, Manlin; Deng, Luxin; Liu, Miao; Cong, Yanguang (Frontiers in Microbiology, 2022)
Enteric fever is caused by Salmonella enterica serovar Typhi, Salmonella enterica serovar Paratyphi A, B and C. While S. Typhi remains the primary causative agent of enteric fever, S. Paratyphi A is responsible for an increasing portion of enteric fever incidence. However, the current available vaccines for enteric fever are all developed from S. Typhi, and lack adequate cross-immune protection against paratyphoid fever A. Therefore, paratyphoid A vaccines are urgently needed. The present paper reviews the latest progresses in pathogenesis, global burden, infection features of paratyphoid fever A, as well as the status of vaccine development, highlighting the necessity for the development of vaccines against paratyphoid fever A.